2020
DOI: 10.1016/j.jcf.2019.10.021
|View full text |Cite
|
Sign up to set email alerts
|

CFTR: New insights into structure and function and implications for modulation by small molecules

Abstract: Structural biology and functional studies are a powerful combination to elucidate fundamental knowledge about the cystic fibrosis transmembrane conductance regulator (CFTR). Here, we discuss the latest findings, including how clinically-approved drugs restore function to mutant CFTR, leading to better clinical outcomes for people with cystic fibrosis (CF). Despite the prospect of regulatory approval of a CFTR-targeting therapy for most CF mutations, strenuous efforts are still needed to fully comprehend CFTR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…If so, the binding site must contain other residues as well, because our K166 mutants (to E or Q) showed a strong response rather than the lack of response expected upon disruption of the drug binding site. To determine the VX-809 binding site, we may need to await high-resolution structures of CFTR complexed with the drug (reviewed in [80]).…”
Section: How Where and When Does Vx-809 Act: Site-of-binding Vs Sitmentioning
confidence: 99%
“…If so, the binding site must contain other residues as well, because our K166 mutants (to E or Q) showed a strong response rather than the lack of response expected upon disruption of the drug binding site. To determine the VX-809 binding site, we may need to await high-resolution structures of CFTR complexed with the drug (reviewed in [80]).…”
Section: How Where and When Does Vx-809 Act: Site-of-binding Vs Sitmentioning
confidence: 99%
“…We therefore speculated that ICL2 coupling to NBD2 may be crucial for CFTR activity. Comparing solvent accessibility of K273 in Cryo-EM models of inactive CFTR 9 (PDB 5UAK) and activated, dimerized CFTR 14 (PDB 5UAR) revealed that K273 was solvent excluded in both models as well as in additional homology models 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Experts in the CF field still maintain that "structural biology and functional studies are a powerful combination to elucidate fundamental knowledge about CFTR and are key for the development of better drugs to enable people with CF to live full and active lives" [44,45]. In addition, scientists are comparing and trying to elucidate the robustness of current methods and markers used to evaluate the benefit of these new modulation therapies [27,46,47].…”
Section: Patient Response To Cftr Modulatorsmentioning
confidence: 99%